Experiment and Numerical Simulation on Damage Behavior of Honeycomb Sandwich Composites under Low-Energy Impact - Xiaoxia Zheng; Bohan He; Yu Zou; Qiao Yang; Yupeng Cao; Zhiqiang Li; Yaokun Han (Aerospace, 2023)
It is well-established that the honeycomb sandwich composite structures are easily prone to damage under low-energy impact. Consequently, it would lead to a dramatic decrease in structural load-bearing capacity and a threat to overall safety. Both experimental and numerical simulations are carried out to investigate the impact damage behavior of honeycomb sandwich composite specimens. The damage mode, damage parameters, and contact force-time curves of three types of panel materials with T300, T700, and T800 are obtained under different impact energies of 10 J, 20 J, and 40 J by the drop-weight impact experiment. Moreover, digital image correlation (DIC) tests are used to measure the deformation and strain of the lower panel. The experimental results reveal that the degree of damage increases with increasing impact energy. Particularly, the T300 panel specimen exhibits visible fiber fracture when subjected to an impact energy of 40 J. The impact process involves matrix cracking, fiber fracture, and delamination of the upper panel occurring first, followed by immediate crush damage to the honeycomb core and, finally, slight fiber damage to the lower panel. Due to its higher strength, the T800 panel specimen exhibits the highest damage resistance compared to the T700 and T300 panel specimens. To consider the microscopic failure criteria and various types of contact during the impact process, a finite element model of honeycomb sandwich composites is established, and numerical simulation analysis of low-energy impact is performed to determine the damage mode, damage size, and contact-force curves. Comparative analysis demonstrates good agreement between the simulation and experimental results. The findings of this study provide valuable technical support for the widespread application of honeycomb sandwich composites in the aviation field.